The effect of Education 4.0 tools on 7th grade students' learning outcomes and attitudes in the electrical circuits unit - Basgul, Melek; Costu, Bayram (SPRINGER, 2025)
Education 4.0 represents a visionary approach to the future of education, aiming to enhance teaching and learning through advanced technologies. The aim of this research is to determine student attitudes toward the use of Education 4.0 tools in the 7th-grade Science course Electrical Circuits unit. To achieve this, an attitude test was developed to evaluate the integration of Education 4.0 tools into the Science curriculum, and student attitudes were assessed using this test. A quasi-experimental design with pre-test and post-test control group, one of the quantitative research methods, was used in the study. The research involved 41 seventh-grade students from one public secondary schools in Turkey, with 21 students in the experimental group and 20 in the control group. The Attitude Scale toward the Use of Education 4.0 Tools in Science Teaching, developed by the researchers, was used as the data collection instrument. The experimental phase lasted four weeks (16 lesson hours), during which the experimental group engaged in activities involving Education 4.0 tools, while the control group followed the curriculum-prescribed activities. The t-test results of the collected data revealed a statistically significant difference between the post-test scores of the experimental and control groups, with the experimental group showing more favorable outcomes. The research findings reveal that students exhibit a positive attitude toward the use of Education 4.0 tools in science education. These results suggest that the integration of Education 4.0 into science education enhances students' understanding of abstract electrical concepts such as electric current, potential difference, resistance, and Ohm's Law, improves knowledge retention, and transforms the learning process into an interactive and discovery-oriented experience. Furthermore, Education 4.0 tools have contributed to the improvement of learning outcomes by promoting student engagement and make learning processes more efficient by improving students' ability to use technology effectively.
Keywords: Education 4.0; Education 4.0 Tools; Education 4.0 Tools Attitude Scale; Electric Circuits; Science Teaching; Student Attitudes; MANAGEMENT; Education & Educational Research